Sustainable growth with pollution augmenting technological changes - Yoon, Sang Won; Yoon, Chang-Ho (2023)
Disruptive technological changes, including carbon capture and storage, can have macroeconomic rebound effects that pose a threat to long term environmental sustainability when not accompanied by pollution taxes. The paper demonstrates that when the elasticity of intertemporal substitution is less than one, implementing a Pigouvian tax effectively stabilizes pollution emissions, regardless of technical and consumption elasticities of substitution. However, if the elasticity of intertemporal substitution exceeds one, flexibility in technical or consumption substitution could cause sustainable growth to falter. The policy implications concerning the role of subsidies for clean technology are discussed.
Keywords: Elasticity of intertemporal substitution; Optimal pollution tax; Sustainable development; dept.eco; energy rebound; technological change